SCADA LIVE FORENSICS: REAL TIME DATA ACQUISITION PROCESS TO DETECT, PREVENT OR EVALUATE CRITICAL SITUATIONS - Pedro Taveras N. (European Scientific Journal, ESJ, 2013)
SCADA (Supervisory Control and Data Acquisition System) systems were originally created to be deployed in non-networked environments. Therefore they lack of adequate security against Internet-based threats and cyber-related forensics. In recent years, SCADA systems have undergone a series of changes that might increase the risks to which they are exposed. Among these risks it can be observed that its increased connectivity may permit remote controls over the Internet, or the incorporation of general purpose tools, thus incorporating already known vulnerabilities of these. Any cyber-attack against SCADA systems demands forensic investigation to understand the cause and effects of the intrusion or disruption on such systems. However, a SCADA system has a critical requirement of being continuously operational and therefore a forensic investigator cannot turn off the SCADA system for data acquisition and analysis. This paper leads to the creation of a high level software application capable of detecting critical situations like abnormal changes of sensor reads, illegal penetrations, failures, physical memory content and abnormal traffic over the communication channel. One of the main challenges is to achieve the development of a tool that has minimal impact over the SCADA resources, during the data acquisition process.